2007
DOI: 10.1128/jcm.02076-06
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Study ofChlamydia trachomatisSerovars among High-Risk Women in China Performed Using PCR-Restriction Fragment Length Polymorphism Genotyping

Abstract: This was one of the first epidemiological studies in China focused on genital Chlamydia trachomatis serotype distribution in high-risk female populations using omp1 gene-based restriction fragment length polymorphism analysis. One thousand seven hundred seventy cervical swab samples from women attending sexually transmitted disease clinics and female sex workers in six cities in China (Shenzhen and Guangzhou in southern China, Nanjing and Shanghai in eastern China, and Nanning and Chengdu in southwestern China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
38
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 23 publications
9
38
4
Order By: Relevance
“…Other studies have demonstrated frequencies of genotype E similar to ours in asymptomatic subjects [24][25]. Even among High-Risk Women in China, serovar E was associated with asymptomatic infection [26]. In Buenos Aires city, Argentina, Gallo Vaullet et al have confirmed an increased frequency of genotype E in neonatal ocular samples and genital adult samples [27].…”
Section: Discussionsupporting
confidence: 81%
“…Other studies have demonstrated frequencies of genotype E similar to ours in asymptomatic subjects [24][25]. Even among High-Risk Women in China, serovar E was associated with asymptomatic infection [26]. In Buenos Aires city, Argentina, Gallo Vaullet et al have confirmed an increased frequency of genotype E in neonatal ocular samples and genital adult samples [27].…”
Section: Discussionsupporting
confidence: 81%
“…Serovars E and F are generally found to be predominant in most countries, including Australia, Netherlands, and Sweden (28)(29)(30)(31)(32). Using omp1 PCR-based restriction fragment length polymorphism genotyping, Lan et al (33) reported that in women Ͻ30 years old, serovars D (4/21 asymptomatic women) and I (4/21 asymptomatic women) were associated with asymptomatic infection, while serovar G was associated with symptomatic infection (4/30 symptomatic cases).…”
Section: Chlamydial Serovars Can Associate With Repeat Infection and mentioning
confidence: 99%
“…circulating within a given community but also sheds light on their global epidemiology, which may assist in developing strategies for improved STD control (14). An immunochromatography test (ICT) that includes monoclonal antibodies to detect lipopolysaccharide antigens extracted from C. trachomatis isolates can be used as a screening test because of its high sensitivity (94z) and specificity (99z) (15).…”
mentioning
confidence: 99%